Mutu Pelayanan Bimbingan Konseling Dalam Mengevaluasi Program Bimbingan Konseling Sekolah Menengah Atas Swasta Budi Satrya Tahun Akademik 2023-2024 - Hayati, Amal; Bayu, Dian Reka; Butar Butar, Nur Fadillah; Lestari Sinaga, Runi Novita (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2023)
The quality of guidance and counseling (GC) services in evaluating the GC program at the private high school Budi Satrya has become the focus of this research. Evaluating the GC program is essential to measure the efficiency, effectiveness, and success of the GC staff in implementing the program. The research results are expected to contribute to the development of knowledge in the field of education, especially in enhancing the quality of GC services in evaluating the GC program.The research findings indicate that the average score of students on the evaluation of the GC program is 84 out of the ideal score of 98. The highest score reached 98, while the lowest score was 62. The method used in this research is quantitative descriptive and statistical data analysis, with data collection through questionnaires filled out by 11th-grade students majoring in science. This research provides insights into the extent to which the GC program at the private high school Budi Satrya has successfully achieved its goals, and this has significant implications for improving the quality of GC services in the school.